Preliminary Phytochemical Screening and Quantitative Analysis of Methanol Leaf Extract of Erlangea tomentosa (Oliv. & Hiern) S.Moore (Asteraceae) - Anselme Mboneye; Albert Nyanchoka Onchweri; Timothy Neeza; Saidi Odoma (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2023)
Various medications are being developed using natural products, particularly those resulting from medicinal plants. So, the screening and quantity analysis of phytochemicals in the methanol leaf extract of Erlangea tomentosa was looked at to find out what chemicals in the plant were responsible for its biological activity. Ten different phytochemicals, such as alkaloids, glycosides, cardiac glycosides, flavonoids, saponins, coumarins, steroids, terpenoids, phenols, and tannins, were found by the analysis. Glycosides and cardiac glycosides were below the limits, and neither phlobatannins nor anthraquinones were found. Quantitative phytochemical analysis showed that there were 3.38g of alkaloids, 2.19g of tannins, 1.81g of flavonoids, and 0.31g of saponins. The concentrations of standard solutions per 100g of crude sample were used to estimate all the results of the tests.